P148 Solriamfetol Titration & AdministRaTion (START): Dosing and titration strategies in patients with narcolepsy starting solriamfetol. (7th October 2021) - Thorpy, M; Hyman, D; Parks, G; Chen, A; Foley, C; Ito, D; Singh, H
Abstract: Introduction: Solriamfetol (Sunosi) is a dopamine/norepinephrine reuptake inhibitor approved (EU/US) to treat excessive daytime sleepiness (EDS) in adults with narcolepsy (75–150 mg/day) or obstructive sleep apnoea (OSA) (37.5–150 mg/day). This study characterised real-world dosing and titration with solriamfetol in patients with narcolepsy. Methods: A retrospective patient chart review was conducted among US-based physicians prescribing solriamfetol. Initiation strategies were de novo (no prior EDS medication), transition (switched/switching from existing EDS medications to solriamfetol), or add-on (adding solriamfetol to current EDS medication). Results: Twenty-three physicians entered data from 70 patients with narcolepsy (type 1, 24/70; type 2, 46/70; mean+/-SD age, 40+/-11 years; 57% female; 6 also had OSA). EDS was mainly moderate (59%) or severe (36%). Nineteen patients (27%) initiated de novo, 31 (44%) transitioned, and 20 (29%) were add-on. Most patients started solriamfetol at 75 mg (86%) and were stable at 150 mg (76%). Most (67%) had 1 dose adjustment; median (range) time to a stable dose was 14 (1–60) days. EDS severity (44% of patients) was frequently considered when titrating. Fourteen of 22 (64%) transitioning from wake-promoting agents (WPAs) stopped them abruptly; 5/9 (56%) using stimulants tapered off. Discussion: In a real-world study, most physicians prescribing solriamfetol to patients with narcolepsy started at 75 mg, tapered stimulants, abruptly discontinued WPAs, and made 1 dose adjustment. Support: Jazz Pharmaceuticals